The effect of an addition of crude palm oil to the density and voids of asphalt mix - Norsyafiqah, Ismail (2018)
The increasing in environmental regulations and high initial cost of asphalt binder has encouraged researchers to modify or replace the alternative binders that can be used for hot mix asphalt (HMA). Asphalt modification acts as an important role in the asphalt industry. In order to achieve the goal of refining binder properties, a chosen additive should produce an interaction within asphalt binders by combining chemically with the binder. Modification of asphalt binders is becoming gradually expensive and difficult due to rise costs of petroleum products. There has been a constant decline in the performing of asphalt pavement properties. Normally, road defect occurred due to high volume of rainfall that will contribute to high road maintenance cost. Therefore, more researches need to be carried out on how to improve the performances of asphalt pavement. There are various types of method used to produce the Hot Mix Asphalt for road pavement such as Marshall Mix Design, Hveem Method and the latest method called Superior Performing Asphalt Pavement or Superpave. While producing the HMA, a mix designs method that includes the laboratory procedures have to be conducted to validate the necessary proportion of the materials to be used. The Marshall Mix Design Method is commonly used for the design of Hot Mix Asphalt (HMA). This study was conducted to determine the potential of crude palm oil as an additive in hot mix asphalt design in order to provide the sufficient wearing course in flexible pavement. The potential of crude palm oil will be determined based on its workability, durability, stability and the strengthens. All of the tests were conducted in the highway laboratory to collect data and determine the Marshall properties of HMA. All the information which related to the procedures, process and techniques used to produce Hot Mix Asphalt with additional crude palm oil will be explained in this study. The information and guideline used to obtain and calculate all the properties of the material for HMA and criteria for the Marshall Mix Design also will be included. In general, all the results should meet the Malaysian Public Works Department.